Sistem Pendukung Keputusan Memilih Facial Foam untuk Kulit Berminyak Pria dengan UTA - Darwis William Nainggolan; Rido Syahputra Silaban; Cantika Audy Damanik; Clara Marsella Pakpahan; Poningsih Poningsih (Graha Mitra Edukasi, 2024)
Facial skin care in men, especially for those with oily skin, is gaining more and more attention in today's society. The problem of oily skin often leads to various problems, including acne and inflammation, which in turn can affect one's appearance and self-confidence. One solution to this problem is the use of Facial Foam, but choosing the right product is often a challenge, especially among men who are less familiar with skincare products. This research aims to develop a Decision Support System (DSS) using the Utility Theory Additive (UTA) Method to recommend Facial Foam that suits the characteristics of oily skin in men. The methodology used includes data collection regarding criteria, sub-criteria, and alternatives through observation and interviews with users. The five main criteria analysed were Product Effectiveness, Side Effects, Price, Packaging, and Availability. The results of the data analysis show that the Pond's Facial Foam product gets the highest rating of 3,443 so that this product makes it a recommended choice for men with oily skin. This research shows that the UTA Method proves to be effective in simplifying the multicriteria decision-making process related to skincare product selection, providing clear guidance for consumers to choose the product that best suits their needs.